An Evaluation of the Pigment Composition of Eighteen Marine Macroalgae Collected from Okha Coast, Gulf of Kutch, India - J.I., N. Kumar; Kumar, R.N.; Bora, A.; Amb, M. Kaur; Chakraborthy, S. (Our Nature, 2010)
Marine algae are one of the most important marine living resources for food, feed and medicine since ancient times in the West. However, due to lack of awareness among the people especially in India, their multifunctional properties have not yet been exploited. This paper deals with the pigment composition and its significant variation found in eighteen different species of marine macroalgae belonging to Chlorophyta, Phaeophyta and Rhodophyta, collected from the coast of Okha, Gulf of Kutch, Gujarat, India. Chlorophyll and carotenoids extraction was done with 80% acetone as solvent while phycoerythrin pigment was extracted using 50mM phosphate buffer (pH 7.0). The highest chlorophyll content was registered in Cladophora fascicularis while carotenoid content was found to be the highest in Sargassum polycustum. Similarly phycoerythrin content was recorded greater in Scinaia farcellata followed by Porphyra necnamessis and Acanthophora delilei Lamour respectively. In terms of chlorophyll content, the maximum chlorophyll a, b as well as total chlorophyll was registered in most of the species of Chlorophyta followed by Phaeophyta and ultimately Rhodophyta. However, carotenoids were registered to be the highest in most of the species of Phaeophyta group. The group wise distribution of carotenoid showed an order: Phaeophyta>Rhodophyta>Chlorophyta. Chl b/Chl a, Car/Chl a and Car/Chl b ratios were also calculated and high ratios were recorded in Liagora erecta, S.polycustum and Padina gymnospora, respectively. Besides, phycoerythrin content showed the following trend in the species of: Rhodophyta>Phaeophyta>Chlorophyta. Emphasis was made to know the variation of different pigments of all eighteen species of marine macroalgae in this paper. Key words: Marine macroalgae, Chlorophyll a, b, Carotenoid, Phycoerythrin. DOI: 10.3126/on.v7i1.2553 Our Nature (2009) 7:48-55